Estilos de crianza y conductas disruptivas en adolescentes de la Unidad Educativa Replica Eugenio Espejo en la ciudad de Babahoyo - Barros Cruz, Génesis Betsabeth (2025)
The main objective of this study is to determine the correlation between parenting styles and disruptive behaviors in adolescents of the Eugenio Espejo Educational Unit of Babahoyo, this research adopts a quantitative approach allowing data collection through the application of the Steinberg parenting styles scale and the CDIS disruptive behaviors scale. For the development of this study there was a population composed of 225 students where a non-probabilistic sampling by convenience was applied, obtaining a representative sample of 92 students between 14 and 18 years of age, of which 47 were male and 45 were female, since these adolescents met the characteristics established for the optimal development of the research. Through the application of the instruments, results were obtained in which the most prevalent parenting style in this study sample is the permissive parenting style represented by 76% while the most frequent disruptive behavior manifested by these students is alteration in the classroom with 43%, which is why the correlation matrix shows a weak negative correlation between the research variables, however, there is a statistically relevant relationship.